Role of Synthesis Repertory in the Individualized Management of Scabies - Sharma, Anmol; Nangia, Mohita; Arora, Dr. Nidhi (Indian Journal of Integrative Medicine, 2026)
Scabies is a highly contagious parasitic dermatosis caused by Sarcoptes scabiei var. hominis, characterized by intense pruritus, nocturnal aggravation, and polymorphic skin eruptions. Despite its easier clinical diagnosis, management remains challenging due to recurrence, reinfestation, and associated psychosocial distress. Homoeopathy approaches scabies as a manifestation of underlying constitutional imbalance rather than merely a local infection. Individualization forms the cornerstone of treatment, requiring careful evaluation of mental, physical, and clinical symptoms. Repertorisation serves as a scientific method to achieve this individualization. The Synthesis Repertory, developed by Frederik Schroyens, represents an advanced and expanded version of Kent’s repertory, integrating classical sources with contemporary clinical additions. Its structured organization, detailed rubrics, and precise modalities make it particularly useful in dermatological conditions such as scabies, where characteristic symptoms must be differentiated from common pathological features. This review aims to explore the role of the Synthesis Repertory in the individualized management of scabies by analyzing its application in symptom conversion, totality formation, and remedy differentiation. The findings suggest that systematic repertorial analysis using the Synthesis Repertory facilitates structured case evaluation and supports individualized remedy selection. When combined with classical homoeopathic principles, it provides a rational framework for managing scabies beyond symptomatic relief.